Role of polar extracts from two quinoa varieties in prevention of steatohepatitis and cardiovascular diseases and improving glucose tolerance in rats. - Sahar Youssef Al-Okbi; Thanaa E Hamed; Tarek A Elewa; Asmaa A Ramadan; Mohamed F El-Karamany; Bakry A Bakry ‎ (Shahrekord University of Medical Sciences, 2021)
Introduction: Steatohepatitis, which is the deposition of fat in the liver with inflammation and starting of necrosis, can induce cardiovascular diseases (CVDs). The aim of this research was to study the preventive effects of steatohepatitis and CVD by ethanol extract of two quinoa varieties (quinoa 1 and hualhuas) in rats. Methods: Phenolic and flavonoid compounds were determined in the extracts utilizing colorimetric and high-performance liquid chromatography techniques. The 2,2-diphenyl-1-picryl-hydrazil (DPPH) scavenging activity was assessed for the extracts. Rats were divided into four groups, the first group was fed on a balanced diet (negative control), and other groups consumed a high fructose-fat diet (HFFD) to induce steatohepatitis and CVD. The second group served as a positive control; however, the third and fourth groups were treated by ethanol extract of quinoa 1 and hualhuas, respectively. Different biochemical changes, as well as liver and heart histopathology, were followed. Results: Results showed significant elevation in liver lipids, plasma malondialdehyde, total cholesterol (T-C), triglycerides and low-density lipoprotein cholesterol with reduction of high-density lipoprotein cholesterol (HDL-C) and total antioxidant as well as a significant increase in T-C/HDL-C in control positive group (P < 0.05) compared to control negative group. Plasma parameters and liver lipids were improved by the extracts; hualhuas was superior concerning the effect on lipid while quinoa 1 was more efficient in reducing oxidative stress. The oral glucose tolerance curve and the histopathology of the liver and heart tissues were improved by both extracts. Total phenolic and DPPH scavenging activity were higher in quinoa 1 than hualhuas. Protocatechuic and rutin were the major identified phenolic acid and flavonoid compounds, respectively in the extracts. Conclusion: Quinoa extracts are able to prevent the progression of steatohepatitis and CVD, and might be beneficial in patients with such diseases.